Hegel and Husserl on Perception. A Phenomenological Dispute - Staiti, Andrea Sebastiano (Bollettino Filosofico, 2024)
In this paper I stage a phenomenological dispute between Hegel and Husserl on the essence of perception. I argue that Hegel’s dialectical reconstruction of perceptual experience in the Phenomenology of Spirit hinges on two problematic assumptions: (1) the properties of perceptual objects are universals; (2) the way in which sensory properties determine perceptual objects is a kind of negation. I challenge both assumptions drawing on Husserl analysis of perception in Experience and Judgment. On Husserl’s account perceptual objects are not originally experienced as “things-of-multiple-properties”, as Hegel would have it, but rather as inarticulate perceptual wholes. Only through explicative contemplation do perceptual properties become salient and when they do so, they do not negate each other or the object but are rather taken up in a special kind of synthesis of partial coincidence. I conclude with a recapitulation and point toward the relevance of the disagreement between Hegel and Husserl for any future discussion of conceptualism and non-conceptualism in the philosophy of perception. Keywords: Conceptualism/Non-Conceptualism, Hegel, Husserl, Perception, Phenomenology